Development of digibook learning media for a comprehensive shooting practice model - Anggi Riri Wahyuni; Roma Irawan; Tjung Hauw Sin; Atradinal Atradinal (JETL (Journal of Education, Teaching and Learning), 2025)
This research is motivated by the low shooting accuracy of female futsal athletes at the Padang Academy Futsal Club and the lack of a structured training model applied by coaches. The purpose of this research is to develop a learning media in the form of a game-based Digibook that contains a comprehensive shooting practice model to improve athletes' shooting skills. The method used is Research and Development (R&D) with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. Data was collected through questionnaires, observations, and structured shooting tests, then analyzed quantitatively and qualitatively. The validation results showed that Digibook obtained a score of 96% from subject matter experts, 86% from coaching experts, and 76% from linguists, with an average validity of 86% in the "valid" category. Early implementation on a small scale shows that Digibook can improve athletes' understanding and motivation in practicing shooting techniques. The conclusion of this study is that Digibook is suitable for use as a learning and training medium to improve the shooting ability of female futsal athletes effectively and systematically